Peran Kepala Sekolah dalam Menumbuhkan Budaya Anti Korupsi di Lingkungan Sekolah - Juwono, Hendro (MOMENTUM : Jurnal Sosial dan Keagamaan, 2025)
Corruption is one of the crucial problems that threatens the sustainability of national development and damages the values ​​of national life. Education is seen as a strategic instrument in forming an anti-corruption character from an early age, with schools as the vanguard in this effort. This study aims to describe the role of school principals in fostering an anti-corruption culture in the school environment. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The results of the study indicate that school principals have a central role in forming an anti-corruption culture, which is reflected in three main functions: as policy makers who establish rules and programs based on integrity values; as educators who instill and provide examples of anti-corruption attitudes to school residents; and as evaluators who routinely assess the effectiveness of anti-corruption programs and practices in schools. These three roles work synergistically in creating a clean, transparent, and integrity-based school environment. Therefore, strengthening the capacity of school principals to carry out these roles is very important to support the national movement to eradicate corruption through education.